Relationship Between Physical Activity and Body Mass Index with Uric Acid Levels in The Community - Harto, Toto; Roni Ferdi; Yudi Budianto; Keken Ariyanto; Ruch, Orokwowy; Alre, Lenchi (Lentera Perawat, 2024)
Physical activity is related to uric acid levels in the blood, and an increase in body mass index (BMI) is associated with an increase in uric acid levels due to increased triglyceride synthesis in the liver associated with increased purine synthesis by new routes, thereby accelerating uric acid production. The results of Riskesdas in 2018 showed the number of joint diseases from the weighted average results in Ogan Komering Ulu Regency was 1,040. This study aims to determine whether there is a relationship between BMI, physical activity, and uric acid levels in the community in Sukaraya Village, East Baturaja District, Ogan Komering Ulu Regency in 2023. This study used an accidental sampling method with a cross-sectional approach and involved 67 respondents with criteria aged between 26 and 45 years, living in Sukaraya Village, being able to read and communicate well, and being willing to be respondents, while the exclusion criteria in this study were not willing to be respondents and could not communicate, and willing to be a respondent, while the exclusion criteria in this study are not willing to be a respondent and cannot be communicated with.  The instruments used were the International Physical Activity Quitioner (IPAQ) questionnaire to measure physical activity, scales to measure body weight and height, and uric acid sticks and digital devices (easytouch) to measure uric acid levels. Data were processed using SPSS and chi-square analysis to determine the relationship between the independent variable and the dependent variable. The results of chi-square data analysis showed a relationship between physical activity and uric acid levels (p-value 0.005) and a relationship between BMI and uric acid levels (p-value 0.000). Physical activity and BMI index correlate with uric acid levels in residents in Sukaraya Village, East Baturaja District, Ogan Komering Ulu Regency. It is necessary to increase knowledge about joint health for the community by providing counseling on joint health and also holding activities such as gymnastics so that physical activity and body mass index can be controlled so as to reduce the risk of high uric acid levels.